2003
DOI: 10.4049/jimmunol.170.5.2488
|View full text |Cite
|
Sign up to set email alerts
|

IL-13 Is Necessary, Not Simply Sufficient, for Epicutaneously Induced Th2 Responses to Soluble Protein Antigen

Abstract: Th2 responses are clearly involved in the pathogenesis of atopic disease. Thus, understanding the factors responsible for Th2 sensitization at sites of allergen exposure, such as airway and skin, is crucial for directing therapeutic or preventive strategies. Contrary to other models of Th2 sensitization to proteins, we have reported that Th2 responses induced by epicutaneous exposure to OVA are IL-4 independent. Combined deficiency of both IL-4 and IL-13 signaling did prevent Th2 generation, suggesting that IL… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

11
77
0

Year Published

2004
2004
2013
2013

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 92 publications
(88 citation statements)
references
References 54 publications
(60 reference statements)
11
77
0
Order By: Relevance
“…Our data are supported by the finding that endogenous IL-13 is necessary for the priming of a Th2 immune response to OVA administered epicutaneously (48) and by the studies of McKenzie et al (49), demonstrating that mice, lacking IL-13, develop blunted Th2 and IgE Ab responses, whereas mice overexpressing IL-13 have increased IgE Ab levels (50). Our data are reminiscent of the model of murine asthma, described by Gelfand and coworkers (51), induced by priming of the immune response through repeated inhalation of OVA.…”
Section: Discussionsupporting
confidence: 79%
“…Our data are supported by the finding that endogenous IL-13 is necessary for the priming of a Th2 immune response to OVA administered epicutaneously (48) and by the studies of McKenzie et al (49), demonstrating that mice, lacking IL-13, develop blunted Th2 and IgE Ab responses, whereas mice overexpressing IL-13 have increased IgE Ab levels (50). Our data are reminiscent of the model of murine asthma, described by Gelfand and coworkers (51), induced by priming of the immune response through repeated inhalation of OVA.…”
Section: Discussionsupporting
confidence: 79%
“…Both of these actions increase eosinophil survival. Second, IL-13 may play a unique role in the induction of the Th2 response by the skin route (37). Indeed, IL-13, more than IL-4, has been shown to be required for the priming of a Th2 response by soluble persistent Ags in the skin.…”
Section: Discussionmentioning
confidence: 99%
“…IL-13 was the major inducer of Th2 responses, being required independent of IL-4 (20). More recent studies have demonstrated that epicutaneous ovalbumin antigen exposure also induces IL-17, which drives the airway inflammation, even in the absence of IL-4 and IL-13 (21).…”
Section: Animal Models Of Chemical and Protein Allergen Skin Exposurementioning
confidence: 99%
“…Models of atopic asthma have likewise shown that epicutaneous allergen exposure with ovalbumin is highly effective at inducing Th2-like sensitization and subsequent lung asthmatic responses after ovalbumin airway challenge (20). IL-13 was the major inducer of Th2 responses, being required independent of IL-4 (20).…”
Section: Animal Models Of Chemical and Protein Allergen Skin Exposurementioning
confidence: 99%